Phosphate fertilization in soy: Potentiality from different sources - Genari, Daiane Almeida (2021)
The purpose of this paper was to evaluate the effects of the conventional mineral and the orgamineral fertilization on the growing and development of the Glycine max (L.) Merril. The experiment was conducted using completely randomized design with two treatments and nine repetitions, being them: Mineral fertilization with phosphor and potassium, and the organomineral fertilization (BRT Organom®). In the 70 days of seeding, the length of the root and some of the aerial part, was evaluated, beside the number of nodules, number of pods, fresh and dry mass of the root, fresh and dry mass of the aerial part, chemical attributes and the basal respiration of the soil. To the variables: length of the aerial part, length of the root and fresh mass of the root, there was no significant difference between the treatments. However, the variable: number of nodules, number of pods, fresh and dry mass of the aerial part, dry mass of the root and soil’s basal respiration. Surpassed in the plants fertilized by the organomineral’s one, in average, the obtained values in the mineral's fertilization treatment. The obtained results in this work show that the use of organomineral’s fertilizer could supply the nutrients requested by the plant, in substitution of the conventional mineral fertilization, being efficient in the growing and development of the soybean, and further consisting in a sustainable strategy to the production.